To solve for r in the equation 9.48 = 2r – –0.7, we start by simplifying the equation:
9.48 + 0.7 = 2r
9.48 + 0.7 = 2r
10.18 = 2r
Next, we divide both sides of the equation by 2 to isolate r:
10.18/2 = 2r/2
5.09 = r
Therefore, r = 5.09.
Solve for r.
9.48 = 2r − –0.7
r =
11 answers
Solve for q.
q + 3
4
= 3
q =
q + 3
4
= 3
q =
To solve for q in the equation (q + 3) / 4 = 3, we start by isolating q on one side of the equation.
(q + 3) / 4 = 3
First, we multiply both sides of the equation by 4 to get rid of the denominator:
4 * (q + 3) / 4 = 3 * 4
(q + 3) = 12
Next, we subtract 3 from both sides of the equation to isolate q:
(q + 3) - 3 = 12 - 3
q = 9
Therefore, q = 9.
(q + 3) / 4 = 3
First, we multiply both sides of the equation by 4 to get rid of the denominator:
4 * (q + 3) / 4 = 3 * 4
(q + 3) = 12
Next, we subtract 3 from both sides of the equation to isolate q:
(q + 3) - 3 = 12 - 3
q = 9
Therefore, q = 9.
Solve for g.
–10 =
g
2
+ –7
g =
–10 =
g
2
+ –7
g =
To solve for g in the equation –10 = (g/2) + –7, we start by isolating g on one side of the equation.
–10 = (g/2) + –7
First, we can simplify the right side of the equation by combining the terms:
–10 = (g/2) - 7
Next, we can eliminate the denominator by multiplying both sides of the equation by 2:
2 * –10 = 2 * ((g/2) - 7)
-20 = g - 14
Next, we can isolate g on one side of the equation by adding 14 to both sides:
-20 + 14 = g - 14 + 14
-6 = g
Therefore, g = -6.
–10 = (g/2) + –7
First, we can simplify the right side of the equation by combining the terms:
–10 = (g/2) - 7
Next, we can eliminate the denominator by multiplying both sides of the equation by 2:
2 * –10 = 2 * ((g/2) - 7)
-20 = g - 14
Next, we can isolate g on one side of the equation by adding 14 to both sides:
-20 + 14 = g - 14 + 14
-6 = g
Therefore, g = -6.
Solve for d.
d − 7
–1
= –2
d =
Questions
d − 7
–1
= –2
d =
Questions
To solve for d in the equation (d - 7)/(-1) = -2, we start by isolating d on one side of the equation.
(d - 7) / (-1) = -2
First, we can multiply both sides of the equation by -1 to eliminate the denominator:
(-1) * (d - 7) / (-1) = -2 * (-1)
d - 7 = 2
Next, we can isolate d on one side of the equation by adding 7 to both sides:
d - 7 + 7 = 2 + 7
d = 9
Therefore, d = 9.
(d - 7) / (-1) = -2
First, we can multiply both sides of the equation by -1 to eliminate the denominator:
(-1) * (d - 7) / (-1) = -2 * (-1)
d - 7 = 2
Next, we can isolate d on one side of the equation by adding 7 to both sides:
d - 7 + 7 = 2 + 7
d = 9
Therefore, d = 9.
Solve for c.
–2.2 =
c + 12.7
3
c =
–2.2 =
c + 12.7
3
c =
To solve for c in the equation -2.2 = (c + 12.7)/3, we start by isolating c on one side of the equation.
-2.2 = (c + 12.7)/3
First, we can multiply both sides of the equation by 3 to eliminate the denominator:
3 * -2.2 = 3 * ((c + 12.7)/3)
-6.6 = c + 12.7
Next, we can isolate c on one side of the equation by subtracting 12.7 from both sides:
-6.6 - 12.7 = c + 12.7 - 12.7
-19.3 = c
Therefore, c = -19.3.
-2.2 = (c + 12.7)/3
First, we can multiply both sides of the equation by 3 to eliminate the denominator:
3 * -2.2 = 3 * ((c + 12.7)/3)
-6.6 = c + 12.7
Next, we can isolate c on one side of the equation by subtracting 12.7 from both sides:
-6.6 - 12.7 = c + 12.7 - 12.7
-19.3 = c
Therefore, c = -19.3.
Solve for b.
3.81 + 3b = 12.81
b =
3.81 + 3b = 12.81
b =
To solve for b in the equation 3.81 + 3b = 12.81, we start by isolating b on one side of the equation.
3.81 + 3b = 12.81
First, we can subtract 3.81 from both sides of the equation to isolate 3b:
3.81 + 3b - 3.81 = 12.81 - 3.81
3b = 9
Next, we can isolate b by dividing both sides of the equation by 3:
3b/3 = 9/3
b = 3
Therefore, b = 3.
3.81 + 3b = 12.81
First, we can subtract 3.81 from both sides of the equation to isolate 3b:
3.81 + 3b - 3.81 = 12.81 - 3.81
3b = 9
Next, we can isolate b by dividing both sides of the equation by 3:
3b/3 = 9/3
b = 3
Therefore, b = 3.